Factors Affecting Student Drop Out Behavior: A Systematic Review - Banaag, Rethse; Sumodevilla, Jasmine Louise; Potane, Joel (International Journal of Educational Management and Innovation, 2024)
Factors affecting student dropout behavior have been investigated overtime.  A lot of factors came out to be affecting this prevalent concern in schools. However, in this study, a systematic review of peer-reviewed, empirical literature and studies published between 2015- 2023 was conducted to identify the common factors affecting student dropout behavior and interventions implemented to minimize dropout rates. This review specifically tackles two key issues: First, what are the common factors affecting student dropout behavior? Second, what are the common initiatives and or interventions in reducing student dropouts? A total of 12 studies were included in the review which passed the PRISMA diagram guidelines, Critical Appraisal Skills Programme (CASP) checklist, and were organized using a literature matrix. Results showed that family, school, school/teacher, lack of guidance and counseling, social, individual, and socioeconomic factors were the common factors influencing student dropout behavior. Additionally, it showed that remedial programs addressing lack of interest, support and resources, improving the school's guidance program, offering mechanisms for support to counteract the impact of poverty, transportation and counseling services, increased funding for disadvantaged students, raising awareness of the consequences of pre-marital sex, enforcing school dropout policies, integrating sex education, and guaranteeing adequate resource availability were common interventions implemented to address these prevalent factors.  The findings emphasized the importance of tailored and contextualized interventions in addressing the specific factors. Further research is needed to identify interventions that tailor-fit each factor to structure a more efficient and effective program to address issues related to student dropouts.